The social-devaluation effect: interactive evaluation deteriorates likeability of objects based on daily relationship - Ariga, Atsunori (Frontiers in Psychology, 2015)
Although previous research has explored the effects of discussion on optimal and collective group outcomes, it is unclear how an individual's preference for an object is modulated by discussion with others. This study investigated the determinants of likeability ratings under two conditions. In Experiment 1, pairs of participants consisting of friends evaluated various photographic images. Under the interactive condition, the participants discussed their impressions of each image for 30 seconds and then independently rated how much they liked it. Under the non-interactive condition, the participants did not interact with each other but instead only thought about their impressions of each image for 30 seconds before rating its likeability. The results indicate that the exchange of impressions between the participants affected the individual likeability ratings of objects. More specifically, the interactive participants generally rated the images as less likeable than did the non-interactive participants (social-devaluation effect). However, in Experiment 2, the effect was eliminated when the pairs consisted of strangers. These findings suggest that shared information modulates individual preferences but only when a daily relationship exists within a group.